Study on Deformation Law of Deep Foundation Pit with the Top-Down Method and Its Influence on Adjacent Subway Tunnel - Yue Gui; Zhenxing Zhao; Xiaqiang Qin; Jianfei Wang (Advances in Civil Engineering)
Based on a long-term comprehensive instrumentation program, the performance of an excavation pit constructed by the top-down method in downtown Kunming was extensively examined. The measured excavation responses included the deflections of diaphragm wall, vertical column movement, slab axial force, building settlement caused by ground deformation, and the influence of pit excavation on the adjacent subway tunnel. This paper analyses the monitoring data of the existing construction stage. Based on the analyses on the data of field and numerical simulation, the following major findings were obtained: (1) the relationship between the measured maximum wall deflection, δhm, and excavation depth, H, in this study is δhm=0.06%H∼0.27%H, which is quite different compared with the relationship of soft-soil pit δhm=0.02%H∼1.2%H, but closer to the normalized curve of rock-socketed pile δhm=0.01%H∼0.45%H and rock-socketed diaphragm wall δhm=0.031%H∼0.129%H. (2) The relationship between the maximum settlement of column (δp) and excavation depth (H) is δp=−0.09%∼0.04%H. The maximum distortion between the diaphragm wall and the column is less than 1/500 of the limit range proposed by Bjerrum. (3) The impact range caused by excavation is about 3.8 times the maximum excavation depth. The ground settlement around the foundation pit is groove type, and the maximum settlement point is located at 2.7 times the maximum excavation depth. (4) The excavation of the foundation pit leads to the maximum vertical settlement of 2 mm and maximum horizontal displacement of 5.2 mm in the subway tunnel; the maximum change of axial force and bending moment are 8.8 kN (the vertical direction) and 6.4 kN·m/m (the horizontal direction), respectively.